Turning Enemies into Friends: Using Reflections to Improve Sound Source Localization - Protasio Ribeiro, Flavio; Ba, Demba; Zhang, Cha; Florencio, Dinei (ICME, 2010)
Sound Source Localization (SSL) based on microphone arrays has numerous applications, and has received significant research attention. Common to all published research is the observation that the accuracy of SSL degrades with reverberation. Indeed, early (strong) reflections can have amplitudes similar to the direct signal, and will often interfere with the estimation. In this paper, we show that reverberation is not the enemy, and can be used to improve estimation. More specifically, we are able to use early reflections to significantly improve range and elevation estimation. The process requires two steps: during setup, a loudspeaker integrated with the array emits a probing sound, which is used to obtain estimates of the ceiling height, as well as the locations of the walls. In a second step (e.g., during a meeting), the device incorporates this knowledge into a maximum likelihood SSL algorithm. Experimental results on both real and synthetic data show huge improvements in range estimation accuracy.
best student paper award